Pengaruh kecemasan terhadap persepsi risiko bahaya covid 19 pada pekerja pasar tradisional - Nur Komariyah; Latipun Latipun; Retno Firdiyanti (Fakultas Psikologi, 2022)
The news about the Covid 19 virus has made people with lower middle socioeconomic status who work in traditional market worried about this virus. How they thinking about covid 19 reflected in their daily behavior at traditional market. They anxiety that reflected by their behavior become predictor how they thinking about the covid 19 virus. The purpose of this study was to determine the effect of anxiety on the perception of the risk of the danger of covid 19 virus. This study is a quantitative research using survey method. There are 166 participant who surveyed by accidental sampling with some criterias; male and female traditional markets worker and aged 18-61 years. The data collected by instruments; Covid 19 Pperceived Risk Scales (CPRS) and State Trait Anxiety Inventory-Trait (STAI-T) and analized using simple regression. The results showed that there was a significant positive effect on anxiety on the perception of the dangers of covid 19 in traditional market workers (r = 0.205, R2 = 0.042, P = 0.008) Keywords : subjective assessment, anxiety as a trait, lower middle socioeconomic